Analysis of I–V-T characteristics of Be-doped AlGaAs Schottky diodes grown on (100) GaAs substrates by molecular beam epitaxy. (April 2022) - Oussalah, Slimane; Filali, Walid; Garoudja, Elyes; Zatout, Boumediene; Lekoui, Fouaz; Amrani, Rachid; Sengouga, Noureddine; Henini, Mohamed
Abstract: The temperature effect on the electrical characteristics of Au/Ti on Beryllium-doped Al0.29 Ga0.71 As Schottky diodes grown on (100) GaAs substrates by molecular beam epitaxy has been investigated for various temperatures ranging from 260 to 400 K. By assuming thermionic emission is the dominant mechanism by which carrier transport occurs in Schottky barriers, the forward and reverse current–voltage ( I − V ) characteristics are analyzed to assess the main Schottky diode electronic parameters, such as ideality factor ( n ), barrier height ( ∅ B ), series resistance ( R S ) and saturation current ( I S ). These parameters are extracted by using different approaches, such as the conventional I − V method, Cheung and Cheung's method and Norde's method. The I − V analysis showed an abnormal behavior, namely an increase of ∅ B and a decrease of n with increasing temperature. This strong dependence of Schottky diode parameters with temperature was attributed to the spatial inhomogeneity at the metal-semiconductor (MS) interface. By assuming a Gaussian distribution of the barrier heights at the MS interface, the inhomogeneity of the barrier height has been successfully explained. In addition, the temperature dependent energy distribution of interface states density (NSS ) profiles was obtained from the forward bias I–V measurements by taking into account the bias dependence of the effective barrier height ( ∅ e ) and n .